ANALISIS PENGELOLAAN ALOKASI DANA DESA DI DESA SIONGGANG TENGAH KECAMATAN LUMBAN JULU KABUPATEN TOBA TAHUN 2020-2022 - Purba, Imelda Rimenda; Sitanggang, Melva; Gultom, Lamtiur Lidia (UNIKA Santo Thomas, 2024)
This study aims to determine whether the Management of Village Fund Allocation in Sionggang Tengah Village, Lumban Julu District, Toba Regency in 2020-2022 has been carried out in accordance with the Regulation of the Minister of Home Affairs Number 113 of 2014. The population of this study is the Budget Report and Realization of Village Income and Expenditure in Sionggang Tengah Village, Lumban Julu District, Toba Regency. The sample of this study is the Budget Report and Realization of Village Income and Expenditure in Sionggang Tengah Village, Lumban Julu District, Toba Regency in 2020-2022. The research methods used are documentation, interview, and questionnaire methods. The data analysis technique used is descriptive data analysis technique. The results of the study on Village Fund Allocation Management in Sionggang Tengah Village, Lumban Julu District, Toba Regency in 2020-2022 are not in accordance with Permendagri 113 of 2014. Because at the planning stage, the community was not directly involved, and at the accountability stage there were no notice boards or other media that made it easier for the community to find out about the management of allocations and villages. The suggestion that can be given is that it is necessary to involve the village community so that there is an opportunity for strategic ideas from the community to enter, and to create notice boards or other media to make it easier for the community to get information about Village Fund Allocations